Efficacy of different piscicides in wanton killing of weed fishes - Goswami, Biswajit; Patra, Samiran (Journal of the Inland Fisheries Society of India, 2021)
Removal of weed fish is a part of intensive aquaculture practices. In present study, trials were conducted to compare the efficacy of different piscicides used in the farmers’ fields for eradication of weed fishes. Three treatments were undertaken to find out the best suited piscicide with respect to effectiveness, environmental hazards and cost involved for removing unwanted predatory and weed fishes during pre- stocking pond management. These treatments included: celphos tablet (Aluminium phosphide) @ 15 kg/ha/ m water, Technology option-I (T-I): commercial grade bleaching powder [Ca(OCl)Cl] (30% chlorine) @ 350 kg ha-1m-1 and Technology option-II (T-II): a combination of urea [CO(NH2 )2] @100 kg ha-1m-1 followed by commercial bleaching powder @175 kg ha-1m-1 after 18-24 hours. Trail was undertaken by the Dakshin Dinajpur KVK in the farmers’ field in Dakshin Dinajpur district of West Bengal. The water pH, fish mortality rate (%), time taken for initiation of distress to the fishes, time for total fish kill, residual toxicity effect and cost for fish toxicants were recorded. It was observed that the initial pH of pond water was 5.5, 5.8 and 6.2 in FP, T-I and T-II respectively and at the end of the toxicity period, pH was 6.0, 7.8 and 7.5 in FP, T-I and T-II respectively. The fish mortality rates were 97%, 95% and 98% in FP, T-I and T-II respectively. The fish distress started after 30 minutes in FP, after 60 minutes in T-I and within 10 minutes in T-II. It was also found that the total fish killing occurred after 90 min, 240 min and 30 min. in FP, T-I and T-II, respectively. T-II exhibited the best result in all the aspects except the cost effectiveness. However, T-II was found advantageous due the ease of operation and quick but the advantages of the present method over the fish toxicants hither to use in India are ease of operation and quick restoration of normal pond conditions. Key words Piscicides; chlorine; urea; residual effect